1050 Association between workplace social capital and job performance: a multilevel study in china. (24th April 2018) - Gao, Junling; Wang, Jing; Yu, Denglai; Dai, Junming; Fu, Hua; Zhu, Yongkai
Abstract : Introduction: Although researchers have recently paid more attention workplace social capital(WSC), which was found to associate with health and health-related behaviours, such as smoking, physical activity and medicine adherence. Theoretically, WSC facilitates to solve collective action problems, so WSC may associate with job performance. However, there was sparse evidence on association between WSC and job performance, and most of them conducted in developed countries. In order to fill the gap, a multilevel study was conducted in shanghai, China. Methods: A cross-sectional study was conducted among 2380 workers from 33 workplace in Shanghai from December 2016 to March 2017. Job performance was measured by The World Health Organisation Health and Work Performance Questionnaire. WSC was measured by Chinese version of Workplace Social Capital Scale. Data were analysed using STATA 13.0. Results: Four-week relative absenteeism was 0.055 (95% CI: 0.045 to 0.065), and relative presenteeism was 1.037 (95% CI: 1.030 to 1.045). Multilevel generalised linear models indicated that individual-level WSC was negatively associated with relative absenteeism ( β =−0.065, 95% CI: −0.100 to −0.029), both individual-level and aggregated-level WSC were positively associated with relative presenteeism ( β =0.038, 95% CI: 0.015 to 0.061; β =0.042, 95% CI: 0.019 to 0.065) after controlling for demographic characteristic and self-rated health. Conclusion: Consistent with previous findings, the current study found that workplace social capital is also associated with job performance in China context. So building workplace social capital may improve job performance.